The Relations of “shi tun” (示屯) during the Reign of Wu-Ding of Shang (≈1250 B.C. - 1222 B.C.) - Jinjing, Xu (Sinología hispánica. China Studies Review, 2019)
In Annals of Spring and Autumn it is stated that: “State affairs are worship and military affairs.” The inscriptions on turtle shells and bones are records of the escapulimancia during the Shang dynasty (≈1600 BC - 1046 BC), and that covers all aspects of life and society. The “tun” (屯) is a unit of measurement used for the turtle shells and bones of the oracle during the Shang dynasty. A shell or a bone is “a pian (丿)”, and a pair is “a tun (屯)”. “Shi tun” (示屯) refers to the “offering of shells and prepared bones”, is one of the important sources of oracular bones. The organization and analysis of reception records in those bones allow us to get to know this dynasty of more than 3,000 years ago from a new perspective. In addition, we can also understand the social status of taxpayers and signatories, through comparisons with the content of other oracular bones.